Chemical modification of sago bark for used cooking oil removal - Low, Jia Ru (Universiti Malaysia Sarawak (UNIMAS), 2014)
An efficient method required for oil spills cleanup remains a challenge to technologies and environmental scientists. Among all the existing solutions or techniques used for oil spills cleanup, sorption is a recommended technique because it is low cost, effective and easy to prepare. Among the variety of sorbents used, sago bark was chosen due to it is renewable and low cost. In this project is study about the effectiveness of chemical modification of sago bark by fatty acids (stearic acid and palmitic acid) in the presence of catalyst via esterification. The product is characterized by FourierTransform Infrared (FTIR), Scanning Electron Microscope (SEM), hydrophobicity test, water and oil sorption capacity. Results show that MSB has good buoyancy and hydrophobicity and high oil adsorption in aqueous systems. Besides, the results also show that palmitic acid bonded with sago bark (MSB 2) has the best sorption capacity (average 1g/g) for used cooking oil in aqueous systems.